2011
DOI: 10.1121/1.3647264
|View full text |Cite
|
Sign up to set email alerts
|

Non-isomorphism in efficient coding of complex sound properties

Abstract: To the extent that sensorineural systems are efficient, stimulus redundancy should be captured in ways that optimize information transmission. Consistent with this principle, neural representations of sounds have been proposed to become “non-isomorphic,” increasingly abstract and decreasingly resembling the original (redundant) input. Here, non-isomorphism is tested in perceptual learning using AXB discrimination of novel sounds with two highly correlated complex acoustic properties and a randomly varying thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
(25 reference statements)
3
11
0
Order By: Relevance
“…If the goal of production is the efficient generation of an integral or combinatoric acoustic property (Kingston et al, 2008), the observed correlation might indicate a type of "trading relation" in reverse: Talkers may compensate for idiosyncratic variation in one cue by scaling the other inversely, essentially never producing "too much" of a combined cue. Similarly, the observed lack of correlation in perception is consistent with an efficient coding model of speech perception in which cue weighting varies as a function of the distribution of cues in the input (Ming and Holt, 2009;Stilp and Kluender, 2011). That is, a listeners' pattern of cue weighting in the present experiment may simply reflect the fact that VOT and onset f0 were uncorrelated in the stimuli they received.…”
Section: Discussionsupporting
confidence: 63%
“…If the goal of production is the efficient generation of an integral or combinatoric acoustic property (Kingston et al, 2008), the observed correlation might indicate a type of "trading relation" in reverse: Talkers may compensate for idiosyncratic variation in one cue by scaling the other inversely, essentially never producing "too much" of a combined cue. Similarly, the observed lack of correlation in perception is consistent with an efficient coding model of speech perception in which cue weighting varies as a function of the distribution of cues in the input (Ming and Holt, 2009;Stilp and Kluender, 2011). That is, a listeners' pattern of cue weighting in the present experiment may simply reflect the fact that VOT and onset f0 were uncorrelated in the stimuli they received.…”
Section: Discussionsupporting
confidence: 63%
“…Following exposure to stimuli capturing these correlated attributes, signal-to-noise ratio (SNR) of spike-rate coding decreased orthogonal to the correlation, while remaining intact along the correlation; and, mutual information of spike coding increased only along the correlated dimension. Like results from Stilp and Kluender (2011), these patterns of activity remained intact in the face of variation in a third unrelated dimension.…”
Section: Learning Correlations Among Stimulus Attributessupporting
confidence: 60%
“…For speech, this process of perceptual organization begins early in life and presumably supports, at least in part, infants' rapid mastery of multiply specified contrasts within their native language environment. To learn about acquisition of sensitivity to correlations among stimulus attributes by adult listeners, Stilp and colleagues (Stilp, Rogers, & Kluender, 2010c;Stilp & Kluender, 2011, 2012 employed novel complex stimuli that varied across two physically independent acoustic attributes: attack/decay (AD) and spectral shape (SS). A stimulus matrix was generated by crossing AD and SS series for which sounds separated by fixed distance in the stimulus space were approximately equally discriminable.…”
Section: Learning Correlations Among Stimulus Attributesmentioning
confidence: 99%
“…The physical acoustics of natural sounds often reveal correlations between acoustic attributes (Lutfi et al, 2011). In auditory perception, the adaptive coding principle is also supported by the results of a set of psychoacoustic experiments that were the inspiration for this study (Stilp et al, 2010;Stilp and Kluender, 2011.…”
Section: Discussionmentioning
confidence: 54%
“…Additional recent support for the active EC hypothesis in the auditory system comes from psychoacoustic studies (Stilp et al, 2010, Stilp and Kluender, 2011 in which subjects either received passive exposure to, or provided continuous discrimination judgments for sets of complex sounds with covarying amplitude attackdecay ratios and spectral-shapes. Following passive exposure, and also over the course of active discrimination, subjects' acuity in discriminating of sounds along the correlated dimensions remained intact, but discrimination of pairs on the orthogonal dimension was significantly impaired when those pairs were proximal to the principle vector of covariance.…”
Section: Introductionmentioning
confidence: 99%